1999
DOI: 10.1105/tpc.11.7.1253
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Arabidopsis Hexokinase in Tomato Plants Inhibits Growth, Reduces Photosynthesis, and Induces Rapid Senescence

Abstract: Sugars are key regulatory molecules that affect diverse processes in higher plants. Hexokinase is the first enzyme in hexose metabolism and may be a sugar sensor that mediates sugar regulation. We present evidence that hexokinase is involved in sensing endogenous levels of sugars in photosynthetic tissues and that it participates in the regulation of senescence, photosynthesis, and growth in seedlings as well as in mature plants. Transgenic tomato plants overexpressing the Arabidopsis hexokinase-encoding gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 335 publications
(100 citation statements)
references
References 63 publications
2
98
0
Order By: Relevance
“…These data, which clearly differ from those obtained with fruit and leaves (Menu et al 2003;Roessner-Tunali et al 2003), mean that hexokinase over expression does not change the metabolic status of the roots to a significant extent. This confirms conclusions drawn by previous authors (Dai et al 1999) indicating that the general phenotype of HK4 plants was mainly due to hexokinase overexpression in shoots rather than in roots. It may be noted that fumarate contents were clearly increased in HK4 roots compared to WT roots.…”
Section: Application To Functional Genomics: Tomato Plants Overexpressupporting
confidence: 94%
See 2 more Smart Citations
“…These data, which clearly differ from those obtained with fruit and leaves (Menu et al 2003;Roessner-Tunali et al 2003), mean that hexokinase over expression does not change the metabolic status of the roots to a significant extent. This confirms conclusions drawn by previous authors (Dai et al 1999) indicating that the general phenotype of HK4 plants was mainly due to hexokinase overexpression in shoots rather than in roots. It may be noted that fumarate contents were clearly increased in HK4 roots compared to WT roots.…”
Section: Application To Functional Genomics: Tomato Plants Overexpressupporting
confidence: 94%
“…Transformation of plants with hexokinase genes has been conducted as a strategy for studying glucose sensing. Thus, several lines of tomato plants overexpressing Arabidopsis hexokinase 1 (HK4, HK37, HK38) and exhibiting high hexokinase activity in correlation with drastic phenotypic modifications (Dai et al 1999) were produced. Recently, comprehensive metabolic profiling studies on leaves and fruits of these transformant lines were conducted using GC-MS, conventional spectrophotometric and liquid chromatographic methodologies (Menu et al 2003;Roessner-Tunali et al 2003).…”
Section: Application To Functional Genomics: Tomato Plants Overexpresmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, previous studies reporting on AtHXK1 overexpression in tomato and Arabidopsis found a decreased expression of photosynthetic genes and an inhibition of growth (Dai et al, 1999; Kelly et al, 2012). This physiological output is similar to the output being characteristic for SnRK1 activity (Baena-Gonzalez et al, 2007), and hence it supports a model of Hxk/T6P/SnRK1-interdependent signaling.…”
Section: Discussionmentioning
confidence: 80%
“…Although senescence occurs in an age-dependant manner in many species (Noode'n, 1988), its initiation and progression can be modulated by a variety of environmental factors such as temperature, mineral deficiency, and drought conditions, as well as by internal factors such as plant growth regulators (Grbić and Bleecker, 1995;Nam, 1997;Weaver et al 1997;Dai et al 1999). It has proved that drought, darkness, leaf detachment, and the hormones abscisic acid (ABA) and ethylene induce leaf yellowing, which is an good indicator of leaf senescence, whereas, to different extent.…”
Section: Introductionmentioning
confidence: 99%